Implementation of Multimedia Based Learning in Memorizing the Short Hadiths in Raudhatul Atfhal Darul Adib Menteng Medan - Maridah Lubis; Ali Imran Sinaga; Afrahul Fadhilah Daulay (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
One of the problem faced in early childhood now is the weakness in memorizing short hadiths. Hadiths is no lesson that can be achieved by just learning it, without making it. A habit to memorizing it since childhood. Hadits learning through memorization can be started from habituation done at home or school, with habituation installed since childhood wiol provide many benefits to children. The study aims to find out how the implementation of multimedia based learning in memorizing the hadith and the impact it causes as well as supporting in memorizing the hadiths in Raudhatul Atfhal Darul Adib Menteng Medan.  This type of research is field research with qualitative descriptive approach the subject of this study Raudhatul Atfhal Darul Adib Menteng Medan students. The result showed that through multimedia based learning in memorizing the short hadiths makes children memorable it will strengthen children’s memory with a sense of heart and build lovw to our prophet Muhammad Saw.